Effects of White Quinoa Polysaccharide on Regulation of Glucolipid Metabolism in Type 2 Diabetic Mice - Yanqing ZANG; Yingying CHUANG; Changyuan WANG; Yang CAO (Shipin gongye ke-ji)
To investigate the hypoglycemic and lipid-lowering effects of white quinoa polysaccharide (WQP) in type 2 diabetic model mice, the mice were divided into model group, polysaccharide group (800 mg/kg) and normal control group. During the experiment, body weight, fasting blood glucose (FBG), and oral glucose tolerance test (OGTT) were measured. After four weeks of continuous feeding, the mice were dissected, and the serum indexes, liver indexes, and short-chain fatty acids (SCFAs) of the mice were determined. The intestinal contents of the mice were analyzed by 16S rRNA sequencing technology. Results showed that compared with diabetic mice, WQP intake could significantly inhibit the increase of body weight and FBG, improve OGTT, and alleviate insulin resistance in diabetic mice. At the same time, the total cholesterol (TC) content of diabetic mice decreased by 19%, and the low-density lipoprotein cholesterol (LDL-C) content decreased by 33%. The intake of WQP also reduced interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) by 21% and 22%, respectively. The contents of catalase (CAT) and glutathione (GSH) were increased by 20% and 24%, respectively. The content of malondialdehyde (MDA) was decreased by 25%. In addition, the intake of WQP significantly increased the content of SCFAs in diabetic mice (P<0.05). The results of 16S rRNA sequencing revealed that the intake of WQP led to an increase in the abundance of the Bacteroidota and a decrease in the Firmicutes in the intestines of diabetic mice. At the genus level, the intake of WQP increased the abundance of Akkermansia genus. Therefore, WQP plays a hypoglycemic and lipid-lowering role by improving the antioxidant capacity and regulating the gut microbiota structure of type 2 diabetic mice.